Trigunas in organizations: Moving toward an east-west synthesis. (August 2015) - Anuradha, MV; Kumar, YLN
The present study tests an alternative and indigenous theory of personality and explores its links with various aspects of organizational behavior. According to the Indian philosophy, trigunas (three trait-like components), namely, sattva, rajas, and tamas, are present in everyone, but it is the relative predominance of one of the three gunas that determines the personality of an individual. Sattva guna is reflected in equanimity, serenity, and poise. Rajas is expressed in high action orientation, ambition, lust, and so on. Tamas is the trait that is manifested in sloth and laziness. The predictive relationship of these three gunas with organizational citizenship behavior, job satisfaction, and job performance (task performance and overall performance) was measured using the method of multiple regression analysis. Data were collected in dyads using 82 mid-level managers and their subordinates working in various Indian banking organizations. Results confirmed that high sattva guna strongly predicted organizational citizenship behavior and high performance but not job satisfaction. Rajas was the second best predictor of these outcome behaviors (except job satisfaction) but was negatively related to them, suggesting that only when rajas was low would these desirable behaviors be exhibited. Tamas did not predict any of the outcome behaviors measured. This Indian perspective on personality has significant implications for cross-cultural management. These implications and limitations of the study are discussed.